Exploring the intercalation chemistry of layered yttrium hydroxides by 13C solid-state NMR spectroscopy - Yanxin Liu; Shijia Jiang; Jun Xu (Magnetic Resonance Letters, 2022)
Layered rare earth hydroxides (LREHs) are a novel class of two-dimensional materials with potential applications in various fields. The exchange reactions with organic anions are typically the first step for the functionalization of LREHs. Although the laminar structures seem to be clear for anion-exchanged compounds, the state of intercalated organic anions and their interactions with cationic rare earth hydroxide layers remain unclear. Herein, we demonstrate that the use of 13C solid-state nuclear magnetic resonance (ssNMR) spectroscopy enables to extract key information on the state of intercalated organic anions such as their local chemical environment, stacking, and dynamics, which are often difficult or impossible to obtain previously. In combination with powder X-ray diffraction and ab initio density functional theory calculations, the intercalation chemistry of two representative layered yttrium hydroxides with selected monovalent organic anions was studied in detail. The products can undergo secondary exchange with a divalent organic anion, depending on the match between the basal spacing of two phases, i.e., the replacement of benzenesulfonate (BS−), 2,4-dimethylbenzene sulfonate (DMBS−), and 4-ethylbenzene sulfonate (EBS−) with 2,6-naphthalene disulfonate (NDS2−) is allowed due to the insignificant change in basal spacing after exchange, while the replacement of very long dodecyl benzene sulfonate (DBS−) and dodecyl sulfate (DS−) with NDS2− is forbidden. The results therefore provide valuable insights into the structure-property relationships of LREH-based functional materials.